Regulation of duodenal mucosal bicarbonate secretion - Odes, Harold Selwyn (Department of Medicine, 2017)
The present research studied the regulation of duodenal bicarbonate secretion in the anaesthetized guinea-pig, using a model that permitted the study of active transport of bicarbonate. It was determined that dibutyryl 3' ,5'-cyclic adenosine monophosphate, vasoactive intestinal polypeptide, prostaglandin E2, carbachol and theophylline are the chief agonists of duodenal bicarbonate secretion. Vasoactive intestinal polypeptide and prostaglandin E2 act directly via distinct receptors on the duodenal enterocytes, activating adenylate cyclase and protein kinase A in sequence to initiate bicarbonate secretion. In addition, there is good evidence that the inositol phospholipid and protein kinase C cascade is also involved, possibly to a lesser extent, since tetradecanoyl-phorbolacetate and prostaglandin F2a were agonists of bicarbonate secretion. Carbachol, using a m-cholinoceptor pathway, stimulates duodenal bicarbonate secretion by releasing vasoactive intestinal polypeptide. Consistent with this finding is the observation that carbachol has no receptors on duodenal enterocytes. The role of the nicotinic pathway in bicarbonate secretion, however, remains uncertain. Duodenal bicarbonate secretion can be inhibited by somatostatin and acetazolamide. Somatostatin selectively suppresses carbachol-stimulated and VIP-stimulated duodenal bicarbonate secretion, but not PGE2-stimulated bicarbonate secretion. Receptors for somatostatin coupled to adenylate cyclase could not be detected on isolated duodenal enterocytes, which strengthens the hypothesis that carbachol does not act directly on these epithelial cells, but via a second transmitter, vasoactive intestinal polypeptide. Carbonic anhydrase activity is necessary for secretion of bicarbonate, since acetazolamide-inhibition of this enzyme decreased bicarbonate secretion, both basal and stimulated by many different agonists. Carbonic anhydrase serves as a common final step in the generation of bicarbonate in duodenal enterocytes. This enzyme was located in the cytoplasm of cells in the villus as well as the crypt cells, implying that bicarbonate secretion occurs along the length of the villus and crypt. In summary, the present research has shown direct stimulation of duodenal bicarbonate secretion by vasoactive intestinal polypeptide, which participates also in themcholinergic pathway, and by prostaglandin E2. Adenylate cyclase and protein kinase A appear to be the intracellular messengers with the primary function of initiating duodenal bicarbonate secretion. However, there is convincing evidence that the inositol phospholipid and protein kinase C cascade also activates this secretion. Somatostatin selectively stops duodenal bicarbonate secretion. Carbonic anhydrase activity in the crypt and villus is required as the final common step in bicarbonate production.